A novel wheeled mobile robots control based on robust hybrid controller: Mixed H2/H∞ and predictive algorithm approach - Sibang Liu; Kuili Liu; Zhen Zhong; Jinghan Yi; Hamdulah Aliev (Journal of King Saud University. Computer and information sciences, 2022)
One of the challenges facing robot tracking is the difficulty of controlling variety types of robots in known and unknown environments. This paper proposes a new strategy of path tracking for a non-holonomic mobile robot subject to kinematic disturbances using model prediction control and H2/H∞ control by Gain-scheduled control law. In this regard, the problem of tracking a mobile robot is expressed in a way that its kinematic error is in the form of linear parameter variable with bounded disturbance. The purpose of the design is to stabilize the controller by solving the linear matrix inequality (LMI) conditions for error tracking model. The following stability conditions are then formulated in such a way that the upper bounds are considered as LMI auxiliary variables. Also with the help of more free matrices, it can reduce conservatism. The target tracking is first designed with the assumption that there is no obstacle in the environment, and then the obstacle avoidance mode is added to the tracer controller, which is done by modifying the optimal state vector definition. In both cases, the system stability check is also performed. Simulation is performed on several predetermined paths, indicating that this strategy is feasible.